Elucidation of the genetic basis of variation for stem strength characteristics in bread wheat by Associative Transcriptomics. (December 2016) - Miller, Charlotte; Harper, Andrea; Trick, Martin; Werner, Peter; Waldron, Keith; Bancroft, Ian
Abstract Background The current approach to reducing the tendency for wheat grown under high fertilizer conditions to collapse (lodge) under the weight of its grain is based on reducing stem height via the introduction ofRht genes. However, these reduce the yield of straw (itself an important commodity) and introduce other undesirable characteristics. Identification of alternative height-control loci is therefore of key interest. In addition, the improvement of stem mechanical strength provides a further way through which lodging can be reduced. Results To investigate the prospects for genetic alternatives toRht, we assessed variation for plant height and stem strength properties in a training genetic diversity panel of 100 wheat accessions fixed forRht . Using mRNAseq data derived from RNA purified from leaves, functional genotypes were developed for the panel comprising 42, 066 Single Nucleotide Polymorphism (SNP) markers and 94, 060 Gene Expression Markers (GEMs). In the first application in wheat of the recently-developed method of Associative Transcriptomics, we identified associations between trait variation and both SNPs and GEMs. Analysis of marker-trait associations revealed candidates for the causative genes underlying the trait variation, implicating xylan acetylation and the COP9 signalosome as contributing to stem strength and auxin in the control of the observed variation for plant height. Predictive capabilities of key markers for stem strength were validated using a test genetic diversity panel of 30 further wheat accessions. Conclusions This work illustrates the power of Associative Transcriptomics for the exploration of complex traits of high agronomic importance in wheat. The careful selection of genotypes included in the analysis, allowed for high resolution mapping of novel trait-controlling loci in this staple crop. The use of Gene Expression markers coupled with the more traditional sequence-based markers, provides the power required to understand the biological context of the marker-trait associations observed. This not only adds to the wealth of knowledge that we strive to accumulate regarding gene function and plant adaptation, but also provides breeders with the information required to make more informed decisions regarding the potential consequences of incorporating the use of particular markers into future breeding programmes.